ВПРОВАДЖЕННЯ ФІНАНСОВОГО КОНТРОЛІНГУ В РАМКАХ УПРАВЛІННЯ АКТИВАМИ ПІДПРИЄМСТВА - Головко, Олена; Омеляненко, Денис; Компанєєць, Олена (Bulletin of Sumy National Agrarian University, 2024)
The article is devoted to the generalization of theoretical aspects and practical recommendations for improving the asset management system in modern conditions. The article considers various models, based on the results of which it is possible to draw a conclusion about the company’s financial condition, solvency and probability of bankruptcy. There are many models by which the company’s financial indicators are calculated, but diagnosis was carried out using Altman’s five-factor model, the discriminant model of O. Tereshchenko, the discriminant model of Lees, the discriminant model of Toffler and Tishaw, and the Beaver coefficient. The problem of Ukrainian enterprises in general is the lack of financial control, which helps to increase the assessment of the financial state of the enterprise. The object of research is the process of creating effective management based on financial controlling technology. The subject of the study is the theoretical, methodological and practical foundations of effective management based on financial controlling at the Kharkivzelenbud enterprise. Financial controlling is a new direction in enterprise management, which allows maintaining the internal balance of the enterprise’s economy and its effective development, through the use of financial management techniques and methods. Modern enterprises are faced with the need to search for the latest technologies and methods for maintaining their financial condition. Financial controlling is just such a tool. The essence of the concept of "financial controlling", its purpose and functions have been studied. Methodical approaches to assessing the effectiveness of financial controlling are considered. The relevance of the study lies in the justification of the need to use modern methods of financial controlling at enterprises. Due to the unstable state of the country’s economy, enterprises should pay attention to improving their organization. Finding goals and strengths. Implementation of strategies that will lead to prosperity and development of the enterprise. Financial controlling serves as a result-oriented tool for improving economic activity.